A METHOD BUILD FUZZY ASSOCIATE MEMORY FOR FUZZY CONTROL PROBLEMS - Ha Pham Thanh; Ho Nguyen Cat; Lan Vu Nhu (ASEAN Journal on Science and Technology for Development, 2008)
Building fuzzy associate memory accordance with control problems has great meaning for control methods  In this paper we propose a method, that build fuzzy associate memory for control problem based on optimal trajectory of control problem, the method developed by theory hedge algebras and genetic algorithm.